Effect of Oxygenated Water and Probiotic Administration on Fecal Microbiota of Rats - INGRID SURYANTI SURONO; ALI KHOMSAN; ENOK SOBARIAH; DARTI NURANI (Microbiology Indonesia, 2010)
Oxygenated water is water with increased concentration of physically dissolved oxygen, and can perform all the same functions as the oxygen absorbed through the lungs. Several structures of human organs participate in the absorption and transportation of the oxygen, including the villi and cells containing mitochondrion in the small intestine as well as the lymph system. The aim of this in vivo study were three folds, to validate the support of oxygenated water on viability of probiotic bacteria in the GUT, to suppress the fecal coliform, and to study the effect of oxygen concentration on the profile of fecal microbiota. There were one control group and three probiotic groups of 5 rats each based on strain of probiotic supplementation, control without probiotic (a0), Lactobacillus casei commercial strain (a1), Lactobacillus sp. IS-7257 (a2) and Lactobacillus sp. IS-27560 (a3). Each group was treated with three variable treatments, without oxygenated water supplementation (b0), supplemented with oxygenated water at 50 ppm (b1), and at 80 ppm (b2). Fecal samples were collected before (c0), after 3 days (c1), 7 days (c2) supplementation, followed by 3 days after returning back to normal diet (c3), analysed by culture dependent analyses for viable fecal lactic, coliform and fecal anaerobic bacteria. Supplementation of oxygenated water at 50 ppm, significantly increase fecal lactic acid bacteria of all probiotic groups after 3 and 7 days (P<0.05); 80 ppm oxygenated water tends to lower the fecal coliform (P<0.1), while oxygenated water administration gives no effect on fecal anaerobic bacteria. As a conclusion, 50 ppm oxygenated water administration significantly increased viable fecal lactic acid bacteria in probiotic groups. On the other hand, 80 ppm oxygenated water administration tends to lower the fecal coliform bacteria. No effect of administration probiotic and/or oxygenated water on viability of fecal anaerobic bacteria.